(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
The article presents the results of a comprehensive phytosociological survey of forest vegetation of garden landscapes of the Middle Pobuzhzhia region, including the establishment of its syntaxonomic structure, revealing of the leading factors of differentiation, analysis of vegetation units and studied parks in terms of species richness and diversity. The data for the study were 90 vegetation plots sampled by the authors on the territory of 15 objects (8 parks-monuments of landscape art of state importance, 5 – local importance, one arboretum of state importance, and one landscape reserve of local importance). The data were analysed using modern quantitative methods of phytosociological research in the environment of the Juice software. As a result of the study, seven vegetation units were obtained, six of them were interpreted to the level of association (Salicetum albae, Urtico dioicae-Alnetum glutinosae, Chelidonio-Robinietum, Tilio-Carpinetum, Isopyro thalictroidis-Carpinetum and Galeobdolo lutei-Carpinetum) and one as a derivative community. The resulted units represent four classes of vegetation - Salicetea purpureae, Alnetea glutinosae, Carpino-Fagetea sylvaticae and Robinietea. The ordination analysis revealed the ecological separation of the derivative community Taraxacum officinale + Fraxinus excelsior, which combined park phytocenoses with the most intensive management, from other vegetation units, as well as the leading role of moisture and continentality in differentiation of the studied vegetation. A comparative analysis on the level of species richness and values of Shannon-Wiener and Simpson diversity indices showed the dependence of these indicators on landscape diversity, managment intensity and area of studied parks. The highest species richness and diversity was observed for floodplain alder forests of the class Alnetea glutinosae, which are very rare in the studied parks. The results of the study can be a theoretical background for planning the management and reconstruction of garden and park landscapes in the region.